ATTORNEY’S REQUEST: PROBLEMS AND THEIR SOLUTIONS (World Bulletin of Management and Law, 2023)
In this article, the concept of an attorney’s request, its subject, the list of entities to which an attorney’s request can be sent, and the terms related to an attorney’s request are comparatively studied and analyzed. The experience of foreign countries regarding the request for an attorney has been analyzed, and proposals for the development of national advocacy legislation have been developed.
Keywords: attorney; attorney’s request; receiving entity; explanation